-11+10(3)=2c

Simple and best practice solution for -11+10(3)=2c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11+10(3)=2c equation:


Simplifying
-11 + 10(3) = 2c

Multiply 10 * 3
-11 + 30 = 2c

Combine like terms: -11 + 30 = 19
19 = 2c

Solving
19 = 2c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-2c' to each side of the equation.
19 + -2c = 2c + -2c

Combine like terms: 2c + -2c = 0
19 + -2c = 0

Add '-19' to each side of the equation.
19 + -19 + -2c = 0 + -19

Combine like terms: 19 + -19 = 0
0 + -2c = 0 + -19
-2c = 0 + -19

Combine like terms: 0 + -19 = -19
-2c = -19

Divide each side by '-2'.
c = 9.5

Simplifying
c = 9.5

See similar equations:

| -7.8+4.8=7x-8.9-6x | | -11+10r=2c | | 4(6+3)+2(1+2)= | | a/b=7/18 | | 9.5+0.25x=9.5 | | (3x/3)^2x | | 935+0.25x=9.5 | | -14x+70= | | X-39+x+6=180 | | x-a=m | | x+24+3x-17-3x-22= | | x+10-y=4198 | | W/25-790=1400 | | 4b(6-7b)=2c | | 3(-1+5x)=-18 | | 4d-1=d+8 | | 10x^4-63x^3+52x^2+63x+10=0 | | 6y^2+12y-30=0 | | -6(x-5)-6=24 | | 4(x-1/2)9 | | (11+x)(16+x)=500 | | 2y-5+3y-7= | | x+3(y)+2(z)=88 | | 2/5x-2=8-13/5x | | x+3x+2x=88 | | x*x=x*x-8 | | 5r^2+42r=27 | | ln(y-3)=8 | | 4(1+2m)=2(5m+8) | | 6.7x+6=3.7x+21 | | -14x+6=-7 | | (11+x)(16+x)=324 |

Equations solver categories